Sustainability accounting education, regulation, reporting and stakeholders - Belal, Ataur Rahman; Cooper, Stuart M.; Giordano-Spring, Sophie; Maurice, Jonathan; Cho, Charles H. (Advances in Environmental Accounting and Management, 2018)
Advances in Environmental Accounting &Managementaims to advance knowledge of the management of corporateenvironmental impacts. It aims to increase the awareness of management accounting practitioners, investors, and other stakeholders of the financial andsocial consequences of corporate environmental impacts